IMPLEMENTASI KEBIJAKAN PROGRAM INDONESIA PINTAR (PIP) DI SMA NEGERI 2 BARRU - Sulfitriani, Sulfitriani; Abdi, Abdi; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2023)
This study aimed to find out the implementation of policies applied to the Smart Indonesia Program; Program Indonesia Pintar (PIP) at SMA Negeri 2 Barru. This study used a qualitative research using 4 informants. Data collection techniques used interviews, observation, and documentation. The results of this study indicated that the Implementation of the Smart Indonesia Program (PIP) in SMA Negeri 2 Barru was quite good. Through several indicators of implementation in this study, namely: 1) policy standards and targets, very helpful for underprivileged students in education, 2) human resources, both facilities and infrastructure were quite good, 3) communication between organizations and strengthening activities, communication between implementers had been good in encouraging the success of PIP policies, 4) Characteristics of implementing agents, existing SOPs were in line with policies, 5). The condition of the PIP policy environment had the support of the school and parents, 6) the disposition of the implementor had implemented the policy implementation well because he understood the existing SOPs.